Factors influencing the spatial distributions of river microbial communities at the watershed scale: a case study involving the Wuding River Basin - Xue, Nan; Xia, Manhong; Hu, Bo; Gong, Xinru; Wang, Zhoufeng; Zhao, Xiaohong (Frontiers in Microbiology, 2025)
Microbial communities regulate water quality and biogeochemical cycling in rivers, but their responses to geomorphological factors remain unclear. Water samples were collected in August 2024 (summer wet season) from the Wuding River, and metagenomic sequencing was used to investigate microbial community changes and the influences of geomorphological factors. Environment (nutrients, etc.,) exhibited significant spatial heterogeneity with temperature (p < 0.01), total organic carbon (TOC, p < 0.001), dissolved organic carbon (DOC, p < 0.001), chemical oxygen demand (COD, p < 0.05), total phosphorus (TP, p < 0.001) and suspended solids (SS, p < 0.001), which were significantly higher downstream than upstream. Pseudomonadota, Cyanobacteriota, and Actinomycetota were the most important microbial phyla, and Cyanobacteriota (p = 0.016) was significantly more abundant upstream than downstream. The linear discriminant analysis effect size (LEfSe) revealed 8 and 10 biomarkers upstream and downstream, respectively. Upstream microbial communities were adapted to oligotrophic and high-light environments, whereas heterotrophic, carbon-metabolizing communities occurred downstream. Significantly higher ACE (p < 0.05), Chao1 (p < 0.05), Shannon (p < 0.001), and Pielou’s evenness (p < 0.001) indices were observed downstream than upstream. The relative abundance of genes associated with carbon cycling (the methane metabolism pathway, TCA cycle, and rTCA cycle) was greater downstream than upstream, as was the relative abundance of nitrogen functional genes. Elevation affected the upstream microbial communities, whereas temperature, TP, TOC, and nitrate nitrogen (NO3-N) affected the downstream communities. The results improve our understanding of how geomorphology drives the environmental factors and then governs the microbial community and their carbon and nitrogen cycling pathways.